The Marketplace for Privacy-Related Products and Services - Nicola Jentzsch (Waterford Institute of Technology (WIT), 2015)
With the large-scale deployment of Information and Communication Technologies markets for products and services related to personal data and privacy are thriving. Yet, to date, there has been little effort to systematically map these markets. In this IPACSO White Paper, a methodology is proposed that enables a systematic horizontal as well as vertical analysis of markets for personal data and privacy-related products and services. This method is applied to classify some of the major players active in these markets.
info:eu-repo/grantAgreement/EC/FP7/609892
Keywords: 650; Datensicherheit; Datenschutz; Marktanalyse